Pengaruh Penggunaan Masker Terhadap Perubahan Flora Residen Kulit Wajah Tenaga Kesehatan Rumah Sakit di Kota Pekanbaru - Adrian Hartanto; Alida Widiawaty; Yuni Eka Anggraini (Fakultas Kedokteran Universitas Riau, 2024)
The use of masks can affect skin characteristics such as temperature, hydration, and acidity. The growth of resident flora on the skin is affected by skin characteristics. This study was to determine the effect of using masks on changes of resident flora hospital health workers’ facial skin. The design of this study was one group pretest-posttest with total sample of 25 people. Results showed that majority of respondents are aged 26-35 years old (52%) and working at Petala Bumi Regional Public Hospital (68%). Results showed that types of resident flora before were Staphylococcus aureus (72%), CNS (100%), and Micrococcus (40%) and after 4 hours using mask were Staphylococcus aureus (60%), CNS (100%), and Micrococcus (24%). Median number of resident flora before and after 4 hours was 346 (17-1314) and 272 (12-1053). Based on statistical tests, there is an effect of using masks on number of resident flora (p value= 0,042).